Comparative performance analysis of image compression by JPEG 2000: a case study on medical images - Shariq, Haseeb; Khalifa, Othman Omran (Asian Network for Scientific Information, 2006)
JPEG 2000 is a new and improved, image-coding standard developed for compression of images. JPEG 2000 is the state-of-the-art image-coding standard that resulted from the joint efforts of the International Standards Organization (ISO) and the International Telecommunications Union (ITU); JPEG in JPEG 2000 is an acronym for Joint Picture Experts Group. The new standard outperforms the older JPEG standard by approximately 2 dB of Peak Signal to Noise Ratio (PSNR) for several images across all compression ratios. Reasons behind JPEG 2000 is superior performance are the wavelet transform and Embedded Block Coding with Optimal Truncation (EBCOT). This study describes the performance comparison of JPEG 2000 against its predecessor JPEG, by evaluating image compressions for medical images. The present research further describes the most important parameters of this new standard in order to help resolve design tradeoffs.